Impact of synthesis temperature and precursor ratio on the crystal quality of MOCVD WSe2 monolayers. (14th May 2023) - Grundmann, Annika; Beckmann, Yannick; Ghiami, Amir; Bui, Minh; Kardynal, Beata; Patterer, Lena; Schneider, Jochen; Kümmell, Tilmar; Bacher, Gerd; Heuken, Michael; Kalisch, Holger; Vescan, Andrei
Abstract: Structural defects in transition metal dichalcogenide (TMDC) monolayers (ML) play a significant role in determining their (opto)electronic properties, triggering numerous efforts to control defect densities during material growth or by post-growth treatments. Various types of TMDC have been successfully deposited by MOCVD (metal-organic chemical vapor deposition), which is a wafer-scale deposition technique with excellent uniformity and controllability. However, so far there are no findings on the extent to which the incorporation of defects can be controlled by growth parameters during MOCVD processes of TMDC. In this work, we investigate the effect of growth temperature and precursor ratio during MOCVD of tungsten diselenide (WSe2 ) on the growth of ML domains and their impact on the density of defects. The aim is to find parameter windows that enable the deposition of WSe2 ML with high crystal quality, i.e. a low density of defects. Our findings confirm that the growth temperature has a large influence on the crystal quality of TMDC, significantly stronger than found for the W to Se precursor ratio. Raising the growth temperatures in the range of 688 °C to 791 °C leads to an increase of the number of defects, dominating photoluminescence (PL) at low temperatures (5.6 K). In contrast, an increase of the molar precursor ratio (DiPSe/WCO) from 1000 up to 100 000 leads to less defect-related PL at low temperatures.